INSTITUTOS FEDERAIS DO NORDESTE E O USO DO TRÂMITE PRIORITÁRIO DE PATENTES PARA ICTs. - Maia do Amaral, Ricardo (2023)
The national system for exploiting industrial property, whose protection works through the granting of registrations and patents, is relevant for the country's technological development. In the case of patents, the large increase in requests received by industrial property offices generates what has been called a backlog. The objective of this work was to verify the degree of adhesion to the program of priority processing of patent processes for depositors of Scientific and Technological Institutions - ICTs, among the eleven Federal Institutes of Education in the Northeast. However, it is perceived that adherence to the priority procedure for ICT patents is still something little explored.